1995
DOI: 10.1002/jhrc.1240180206
|View full text |Cite
|
Sign up to set email alerts
|

A study of the compositional variation of the essential oil of ylang‐ylang (Cananga odorata Hook Fil. et Thomson, formagenuina) during flower development

Abstract: SummaryVolatile secondary metabolites from Colombian ylang-ylang flowers were obtained by combined steam distillation -solvent extraction. The samples were analyzed by high resolution gas chromatography with flame ionization, nitrogedphosphorus, or mass spectrometric detection. The chemical composition of the oils extracted from flowers at different stages of development differed both qualitatively and quantitatively. The generation of total volatile metabolites, light oxygenated compounds in particular, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 6 publications
1
21
0
3
Order By: Relevance
“…When different C. odorata flower parts were extracted separately, it was found that on changing from petals to ovaries, the monoterpene and sesquiterpene contents increase, while light-and heavy-oxygenated compounds decline [5]. Oils obtained from fully developed C. odorata flowers contained 16 and 4 times more light-and heavy-oxygenated compounds, respectively, than those obtained from green undeveloped flowers, rich in monoterpene and sesquiterpene hydrocarbons [6]. The extraction technique plays a significant role in determining the composition of the isolated volatiles mixture.…”
Section: Introductionmentioning
confidence: 95%
“…When different C. odorata flower parts were extracted separately, it was found that on changing from petals to ovaries, the monoterpene and sesquiterpene contents increase, while light-and heavy-oxygenated compounds decline [5]. Oils obtained from fully developed C. odorata flowers contained 16 and 4 times more light-and heavy-oxygenated compounds, respectively, than those obtained from green undeveloped flowers, rich in monoterpene and sesquiterpene hydrocarbons [6]. The extraction technique plays a significant role in determining the composition of the isolated volatiles mixture.…”
Section: Introductionmentioning
confidence: 95%
“…Romero y albahacas, tomillo y mentas, anís [1], orégano [2], mejorana, ruda [3,4], provienen del Mediterráneo; limonaria y citronela [5], jengibre, cítricos [6][7][8], vetiver, ylang-ylang [9][10][11], patchoulí (pachulí) llegaron de Asia, geranio, del sur de África; pero, hoy en día, estas son plantas comunes en Colombia, asilvestradas o cultivadas, que se utilizan ampliamente con diferentes propósitos, tanto en medicina popular, como en culinaria.…”
unclassified
“…En el Centro Nacional de Investigaciones para la Agroindustrialización de Especies Vegetales, Aromáticas y Medicinales Tropicales, CENIVAM, se han estudiado sistemáticamente varias especies vegetales aromáticas tanto exógenas [1][2][3][4][5][6][7][8][9][10][11], como nativas, entre estas, Copaifera officinalis [17], Spilanthes americana [18], Lepechinia schiediana [19], Lippia alba [20], Xylopia aromatica [21], Hyptis umbrosa [22], Callistemon speciosus [23] y Lippa origanoides [24]. En estos estudios, se ha hecho el énfasis muy especial en la comparación de métodos de extracción de metabolitos secundarios volátiles [3, 11, 17-21, 25, 26], en el análisis de aceites esenciales y fracciones volátiles por cromatografía de gases (GC) con diferentes sistemas de detección [4,7,18]; así mismo, en el estudio de la transformación catalítica de aceites [1, 8,17] y en la investigación de la actividad biológica de extractos y aceites obtenidos [2,19,20,23,24,27,28].…”
unclassified
“…Forty-nine different components have been identified by gas chromatography-mass spectrometry (GC-MS). Major components to list are linalool, linalyl acetate, eugenol, methyleugenol and methyl benzonate (9)(10)(11). In Brazil, methyleugenol is used in folk medicine as a stomachic and intestinal antispasmodic; it suggests YYEO makes smooth muscle of gastrointestinal system relax (7).…”
Section: Discussionmentioning
confidence: 99%
“…It can also be used as intestinal antispasmodics (7,8). Recent studies indicate the some components in YY oil have vasodilator properties and relaxing effects on smooth muscle (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%